(untitled) - Matsumoto, Michihiro (Tokyo, 1988)
The key to success in Japan is a thorough understanding of the workings of "haragei" - an idea affecting language, social interaction, and business dealings in particular. This volume examines the idea of "haragei"
Keywords: Japan; History